Early- and whole-life exposures to florfenicol disrupts lipid metabolism and induces obesogenic effects in zebrafish (Danio rerio). (December 2022) - Li, Xinhui; Zhao, Fei; Fu, Chen; Yang, Yanyu; Xu, Qianru; Hao, Yinfei; Shi, Xueqing; Chen, Dong; Bi, Xuejun; Gong, Zhilin; Wu, Shujian; Zhang, Haifeng
Abstract: Florfenicol (FF), a widely used veterinary antibiotic, has been frequently detected in both aquatic environments and human body fluids. As a result, there is a growing concern on its health risks. Previous studies have revealed various toxicities of FF on animals, while there are relatively limited researches on its metabolic toxicity. Herein, by employing zebrafish as an in vivo model, endpoints at multiple levels of biological organization were measured to investigate the metabolic toxicity, especially disturbances on lipid metabolism, of this emerging pollutant. Our results indicated that early-life exposure (from 2 h past fertilization (hpf) to 15 days past fertilization (dpf)) to FF significantly increased body mass index (BMI) values, staining areas of visceral lipids, and triacylglycerol (TAG) and total cholesterol (TC) contents of larvae. Further, by analyzing expression patterns of genes encoding key proteins regulating lipid metabolism, our data suggested that promoted intestinal absorption and hepatic de novo synthesis of lipids, suppressed TAG decomposition, and inhibited FFA oxidation all contributed to TAG accumulation in larvae. Following whole-life exposure (from 2 hpf to 120 dpf), BMI values, TAG and TC contents all increased significantly in males, and significant increases of hepatic TAG levels were also observed in females. Moreover, FF exposure interfered with lipid homeostasis of males and females in a gender-specific pattern. Our study revealed the obesogenic effects of FF at environmentally relevant concentrations (1, 10, and 100 μg/L) and therefore will benefit assessment of its health risks. Additionally, our results showed that FF exposure caused a more pronounced obesogenic effect in zebrafish larvae than adults, as suggested by significant increases of all endpoints at individual, tissular, and molecular levels in larvae. Therefore, our study also advances the application of zebrafish larval model in assessing metabolic toxicity of chemicals, due to the higher susceptibility of larvae than adults. Graphical abstract: Image 1 Highlights：: Early- and whole-life exposures to FF caused lipid accumulation in zebrafish. FF induced a more pronounced obesogenic effect in zebrafish larvae than adults. FF disturbed TAG de novo synthesis, FFA oxidation, and fat decomposition in larvae. FF disturbed lipid homeostasis of males and females in a gender-specific pattern.